The myth of gravity concentration to eliminate mercury use in artisanal gold mining. Issue 1 (March 2021) - Martinez, Gerardo; Restrepo-Baena, Oscar Jaime; Veiga, Marcello M.
Highlights: Article reviews gravity separation and concentration interventions implemented globally in AGM. Gravity concentration can reduce the amount of material to be amalgamated. Gravity concentration can potentially eliminate the use of mercury in very rare, specific cases. Article concludes that gravity concentration is not the final solution to eliminate mercury. Abstract: Artisanal and small-scale gold mining (ASGM) continues to expand rapidly due to the increasing global price of gold and the economic impacts of COVID-19. This expansion of ASGM has raised concerns about mercury use and increased the number of projects designed to reduce or eliminate the use of mercury in ASGM in many developing countries. Unfortunately, to date, these projects focusing on substituting mercury with gravity separation or concentration have been relatively unsuccessful due to a lack of continuous support, guidance, and capital. Through a critical examination of the gravity separation and concentration interventions that have been globally implemented in ASGM, the shortcomings and challenges for artisanal miners are addressed. This article highlights how gravity concentration can reduce the amount of material to be amalgamated or treated thermally or chemically to extract gold from concentrates. However, it also acknowledges that this process has the potential to eliminate the use of mercury in very rare, specific cases. Ultimately, this article concludes that gravity concentration is not the final solution to eliminate mercury use in artisanal gold mining, but it can drastically reduce the use of mercury and its release into the environment.